2004
DOI: 10.1679/aohc.67.417
|View full text |Cite
|
Sign up to set email alerts
|

Role of stromal-epithelial interactions in hormonal responses

Abstract: prostate (squamous metaplasia). The mechanistic basis of these stromal-epithelial interactions is poorly understood, but growth factors appear to be mediators of these cell-cell interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
193
0
18

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(222 citation statements)
references
References 72 publications
11
193
0
18
Order By: Relevance
“…Progesterone receptor expression remained high in these areas, however, and both ERa and PR were often highly expressed in the underlying stroma. Recent studies utilizing receptor knockout mouse models have demonstrated that hormone-induced epithelial proliferation can be mediated by stromal receptors in a paracrine manner (Cunha et al, 2004). Similar to previous findings in harbor seals, squamous differentiation was most often noted during late estrus, further suggesting hormone involvement (Bigg and Fisher, 1974).…”
Section: Estrogen and Progesterone Receptor Expressionsupporting
confidence: 73%
“…Progesterone receptor expression remained high in these areas, however, and both ERa and PR were often highly expressed in the underlying stroma. Recent studies utilizing receptor knockout mouse models have demonstrated that hormone-induced epithelial proliferation can be mediated by stromal receptors in a paracrine manner (Cunha et al, 2004). Similar to previous findings in harbor seals, squamous differentiation was most often noted during late estrus, further suggesting hormone involvement (Bigg and Fisher, 1974).…”
Section: Estrogen and Progesterone Receptor Expressionsupporting
confidence: 73%
“…Immunohistochemical analysis of PR expression in the Mig-6 d/d mice showed that epithelial PR expression is not altered but that PR expression in the endometrial stroma cells is significantly reduced. P4 attenuates E2 regulation of proliferation and gene expression by regulating the expression of a yet-to-beidentified paracrine signal from the stromal cells to the epithelial cells (41,42). However, the increase in ER␣ target gene expression at 8 weeks of age was not the result of a change in ER␣ or coactivator level (data not shown).…”
Section: Downregulation Of Mig-6 In Human Endometrialmentioning
confidence: 89%
“…In the human or rodent prostate, the prostate gland is composed of not only epithelial cells but also stromal cells, endothelial cells and immune cells [55][56][57][58]. The epithelium requires the support of the stromal cells for epithelial differentiation, proliferation and apoptosis.…”
Section: In Vitro Epithelium-stroma Co-culture Systems and In Vivo Anmentioning
confidence: 99%